Profitability: Impact of Institutional Ownership, Managerial Ownership and Capital Structure in the Agricultural Sector in Indonesia - Hertina, Dede; Mawarnie, Devy; Ichsani, Sakina (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted to examine the effect of institutional ownership, managerial ownership, and capital structure on profitability in the agricultural sector listed on the Indonesia Stock Exchange for the period 2013-2017. The research population is in agricultural companies listed on the Indonesia Stock Exchange in the period 2013-2017. The sample selection uses a purposive sampling method, and there are 10 companies that fit the sample criteria. The data analysis method uses panel data with the results of partial hypothesis testing showing that institutional ownership does not affect profitability with a probability level of 0.3423. Managerial ownership influences profitability with a probability level of 0.0489. Capital structure has a negative and significant effect on profitability with a probability level of 0.0002. The use of a large debt will reduce the profit generated by the company because of the amount of interest that must be paid by the company for the company’s debt.